Development of a wireless multichannel neural data transmission system - Mukati, Muhammad Rizwan (İstanbul Medipol Üniversitesi Fen Bilimleri Enstitüsü, 2017)
Implantable microelectrode arrays enable multichannel electrophysiological recordings from the mammalian brain during behavioral experiments. Wireless data transmission systems combined with the microelectrode arrays and electrophysiology hardware allow the chronically-implanted subjects to freely move during the neural recording sessions. In the present study, a wireless neural data recording system is designed and implemented to collect data from behaving rats. The system is based on an amplifier chip and a microcontroller with 802.11 technology at the client side, and a PC equipped with LabVIEW software at the server side. The system enables data throughput up to 6.4 Mbps for signals obtained from 16 channel microelectrode arrays with a sampling rate of 25 KHz per channel. Based on five recording sessions each lasting 12.8 seconds, 9927.6 UDP packets ± 105.85 out of 10000 packets each consisting of 1024 bytes were received and recorded by the server. The present system offers a cost-effective and compact solution to perform multichannel in vivo electrophysiological recordings from behaving rats. We also provide the design and 3D models of silicon-based micro-machined microelectrode arrays for extracellular neural signals from 8-32 channels and evaluate the mechanical strength of these probes using simulations.

Bu çalışmada, uyanık sıçanların sinirsel aksiyon-potansiyelinin iletilmesi için kompakt boyutlu kablosuz bir verici sistemi tasarlanıp, üretilmiştir. IEEE 802.11 teknolojisini kullanan sistem 16 ayrı mikro elektrottan alınan veriyi 6.4 Mbps hızında yollayabilmektedir. Deney hayvanlarına dolaşma imkanı veren bu sistem onların stres seviyesini düşürerek daha başarılı ölçümleri mümkün kılmaktadır. Ayrıca, çalışmanın ikinci kısmında silikon tabanlı mikro-işlenmiş mikroelektrotların tasarımı açıklanmıştır. Yani tasarımlar sinirlerden 32 kanala kadar sinyallerin düşük gürültü ile alınmasına imkan vermektedir.
Kablosuz çok kanallı sinirsel veri iletim sisteminin geliştirilmesi